Adapting student practice placements in response to COVID-19: 'Get there together' a digital stories project for people living with dementia. Issue 1 (2nd January 2022) - Clarke, Maria; Rowlands, Rachel; Morecroft, Sarah; Begum, Samira; Evans, Jennifer; Ford, Abigail; Morgan, Jordan; Prior, Isobel; Slater, Caitlin
ABSTRACT: The impact of COVID-19 has been harshly felt by occupational therapists in practice and students requiring practice education placements. A collaboration between Aneurin Bevan University Health Board (ABUHB) and Cardiff University enabled 10 undergraduate students to undertake their final placement by participating in a Digital Stories Project. This placement was innovatively designed to allow students to meet their learning objectives remotely, reducing clinical days in adherence to social distancing measures. The 'Get There Together' project was created by the national steering group after identifying the devastating impact COVID-19 had on people affected by dementia when accessing community occupations. The students collaborated with service users to identify areas that they wanted to visit, creating digital recordings explaining what to expect due to COVID-19 rules. This paper will focus on the conception and development of the Digital Stories Project, which helped increase placement capacity for occupational therapy students, during the COVID-19 pandemic.